Measuring Business Cycles: Approximate Band-Pass Filters for Economic Time Series - Baxter, Marianne; King, Robert G. (The Review of Economics and Statistics, 1999)
Band-pass filters are useful in a wide range of economic contexts. This paper develops a set of approximate band-pass filters and illustrates their application to measuring the business-cycle component of macroeconomic activity. Detailed comparisons are made with several alternative filters commonly used for extracting business-cycle components.